The Relationship of the Clinical Practice Environment, Supervision and Supervisors with Students' Clinical Experience as an Effort to Prepare Professional Nurse Graduates - Devi Susanti; Herlitawati; Taufik Hidayat; Yusnaini (Universitas Ahmad Dahlan, 2023)
Background: Learning turns theoretical knowledge into practice for nursing students. The quality of a student's clinical experience is influenced by the practice environment, supervision, and supervisor. The clinical practice environment influences the approach and achievement of student competencies. Supervision is important for quality nursing care, while effective supervisors act professionally and guide students in managing patients. This study aims to analyze the relationship between the clinical practice environment, supervision and supervisors with the clinical experience of students as an effort to prepare professional nurse graduates in the D-III Nursing study program in Kutacane, Poltekkes Kemenkes Aceh, totaling 64 students with a sampling technique, namely total sampling based on inclusive criteria. Methods: Type of research This is a correlational analytical descriptive with a cross sectional approach. Data analysis was carried out via Univariate and Bivariate. Results: The results of this research show that there is a significant relationship between the clinical practice environment, supervision and supervisors with the clinical experience of students in the D-III Nursing study program in Kutacane, Poltekkes Kemenkes Aceh with p-values of 0.033, 0.024 and 0.015. Conclusion: Therefore, it is recommended that collaboration between educational institutions and health institutions be strengthened to create an optimal clinical practice environment.